The Prevalence of Helicobacter Pylori babA, homB, aspA, and sabA Genes and Its Relationship with Clinical Outcomes in Turkey - Nimet Yılmaz; Meltem Koruk Özer (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. The cag A and vac A genes of Helicobacter pylori (H. pylori) are closely associated with the pathogenicity of bacteria. However, the significance of H. pylori babA, homB, aspA, and sabA genes is not clear in phenotypic characteristics of virulence. This study aimed to investigate the frequency and importance of these genes in patients with H. pylori positive peptic ulcer (PU). Materials and Methods. Patients with a PU or nonulcer dyspepsia (NUD) based on the upper gastrointestinal (UGI) endoscopy findings were included in the study. Biopsy samples from antrum and corpus were cultured into Columbia agar. H pylori were characterized by urease, catalase, oxidase test, and gram staining. Genomic DNA was extracted and stored. The babA, homB, aspA, and sabA genes were determined by using polymerase chain reaction analysis. Results. A total 214 patients were included (99 PU and 115 NUD) and H. pylori could be isolated in 82 patients (36 PU and 46 NUD). The frequency of the babA (25% vs. 15.2%, p=0.25), homB (2.7% vs. 4.3%, p=1), aspA (69.4% vs. 73.9%, p=0.2), and sabA (2.7% vs. 10.8%, p=0.88) genotypes was not different between PU and NUD patients. There were some correlations between the presences of these genes. Conclusion. This study managed to determine babA, homB, aspA, and sabA genes of H. pylori by PCR. However, the frequency of these factors was not different in patients with PU and NUD. There is no role of babA, homB, aspA, and sabA genes for the development of peptic ulcer in Turkish population.